The effects of autoclave sterilization on the cyclic fatigue resistance of ProTaper Universal, ProTaper Next, and ProTaper Gold nickel-titanium instruments - Taha Özyürek; Koray Yılmaz; Gülşah Uslu (Korean Academy of Conservative Dentistry, 2017)
Objectives It was aimed to compare the cyclic fatigue resistances of ProTaper Universal (PTU), ProTaper Next (PTN), and ProTaper Gold (PTG) and the effects of sterilization by autoclave on the cyclic fatigue life of nickel-titanium (NiTi) instruments. Materials and Methods Eighty PTU, 80 PTN, and 80 PTG were included to the present study. Files were tested in a simulated canal. Each brand of the NiTi files were divided into 4 subgroups: group 1, as received condition; group 2, pre-sterilized instruments exposed to 10 times sterilization by autoclave; group 3, instruments tested were sterilized after being exposed to 25%, 50%, and 75% of the mean cycles to failure, then cycled fatigue test was performed; group 4, instruments exposed to the same experiment with group 3 without sterilization. The number of cycles to failure (NCF) was calculated. The data was statistically analyzed by using one-way analysis of variance and post hoc Tukey tests. Results PTG showed significantly higher NCF than PTU and PTN in group 1 (p < 0.05). Sterilization significantly increased the NCF of PTN and PTG (p < 0.05) in group 2. PTN in group 3 had significantly higher cyclic fatigue resistance than PTN group 4 (p < 0.05). Also, significantly higher NCF was observed for PTG in group 2 than in groups 3 and 4 (p < 0.05). Conclusions PTG instrument made of new gold alloy was more resistant to fatigue failure than PTN and PTU. Autoclaving increased the cyclic fatigue resistances of PTN and PTG.